Anatomy & Physiology - Thibodeau, Gary A., 1938-; Patton, Kevin T. (St. Louis ; London : Mosby, 1993)
Designed for the student beginning anatomy and physiology, the second edition of this text takes a body systems approach. It features a mini-atlas of human cadaver dissection and integrates health issues, exercise and fitness, diagnostic studies and other general topics.
Includes bibliographical references and index.
Keywords: Human physiology; Human anatomy; Anatomy; Physiology